Forestry in the Andaman and Nicobar Islands - Banerji, J. (Indian Forester, 1954)
With an area of 3,107 sq. miles distributed over about 183 islands in the Bay of Bengal, the Andaman and Nicobar Islands have an equable climate with high rainfall. While the settlement was established in 1788 the Forest Department has been operating since 1883. Departmental operation has been the keynote of exploitation, and valuable timbers like Padauk, Gurjan and Silvergrey found purchasers from an early date. After the islands were taken over from the Japanese in 1945, a large 8 feet Band Saw-mill has been set up with a potential capacity of 50,000 tons. At present about 58,000 tons are extracted annually. The Indian demands for ’Matchwoods’ and ’Plywoods’ are satisfactorily met; surplus timber is exported to U.K., U.S.A. and other foreign countries. North Andamans forests have been leased out for 25 years. Treated Mangrove poles are exported to the mainland. Recently about 569 refugee families have been settled on 2,845 acres of cleared agricultural land inside the forests. The natural regeneration methods of these tropical rain forests have been satisfactorily solved by the" Canopy-lifting, Shelterwood system" of the Andamans. When the full silvicultural yield of 150,000 tons is exploited, during the Second Five-Year Plan of India, the annual revenue is likely to be Rs. 200 lacs, against about Rs. 60 lacs now.